Identifikasi struktur kognitif siswa dengan menggunakan peta konsep pada larutan asam-basa - Bela Ganda; John Z Lombok; Jenny Kumajas (Oxygenius Journal Of Chemistry Education, 2019)
Every student has different cognitive structures, but few teachers realize these differences. The purpose of this research is to identify students’ cognitive structures, which comprise of several aspects such as content, students’ prior knowledge, new knowledge and misconception when they learn from a concept map. The method used is descriptive research, conducted on 18 students at a senior high school in Manado City. The students’ cognitive structures are revealed using questions from concept map about acid-base solution. The cognitive structures are identified based on the scores obtained by each students from the concept map questions. The result shows three cognitive categories of students on the content aspect, namely poor, good, and excellent, and three categories of students’ cognitive structures, which are students’ prior knowledge, new knowledge and misconception. In general, the students’cognitives structure are categorized as good.